Research on a novel Fabry–Perot interferometer model based on the ultra-small gradient-index fiber probe - Wang, Chi (2019)
A novel Fabry–Perot (F–P) interferometer model based on the ultra-small gradient-index (GRIN) fiber probe is investigated. The signal arm of the F–P interferometer is organically combined with the ultra-small GRIN fiber probe to establish the theoretical model of the novel F–P interferometer. An interferometer experimental system for vibration measurements was built to measure the performance of the novel F–P interferometer system. The experimental results show that under the given conditions, the output voltage of the novel interferometer is 3.9 V at the working distance of 0.506 mm, which is significantly higher than the output voltage 0.48 V of the single-mode fiber (SMF) F–P interferometer at this position. In the range of 0.1–2 mm cavity length, the novel interferometer has a higher output voltage than an SMF F–P interferometer. Therefore, the novel F–P interferometer is available for further study of the precise measurement of micro vibrations and displacements in narrow spaces.